PENGEMBANGAN BAHAN AJAR IPS BERBASIS MODEL LEARNING CYCLE UNTUK MENDUKUNG KOMPETENSI PROFESIONAL MAHASISWA PGSD - Laila Fatmawati (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
This study is research and development adopting Borg & Gall model. The aim ofthis study is to develop of teaching materials based on learning cycle model and thefeasibility of teaching materials. This first year development is limited to three stages:1) the preliminary study and information collection, 2) planning, 3) the initial productdevelopment and validation by experts. The research instrument used was validationsheet, questionnaire sheet, and observation sheet. The data was analyzed by descriptivestatistics technique. The results of the study are: 1) the developed product is module ofSocial Science learning material based on learning cycle on the subject of naturalphenomena and that mitigation, 2) validation by experts showed that the developedteaching material module is very feasible to be used for lectures in Social ScienceLearning Materials in Elementary School so that it could support the professionalcompetence of the college students of Elementary School Education Department, UAD.Keywords: teaching material, learning cycle, professional competence.